Language, Body, and Accountability in Sūrat al-Qiyāmah: A Linguistic-Anthropological Study of Personhood and Intention - Nur Huda; Mas Tajuddin Ahmad; Mowafg Abrahem Masuwd (Indonesian Journal of Arabic Studies, 2026)
Purpose: Existing studies on Sūrah al-Qiyāmah have generally examined eschatology, resurrection theology, rhetorical structure, and textual coherence. These approaches clarify important aspects of the surah, but they have not sufficiently explained how language, bodily signs, self-testimony, intention, and accountability operate together in the Qur’anic construction of personhood. This article therefore examines Sūrah al-Qiyāmah as a Qur’anic discourse that presents humans as embodied, linguistic, intentional, and morally responsible subjects. Methods: The study employs qualitative library research with a linguistic-anthropological approach. The corpus is delimited to Q.75:1–40, especially verses concerning al-nafs al-lawwāmah, bodily reconstruction, self-testimony, excuses, tongue discipline, facial signs, death, and return to God. Data were selected at the level of verses, key lexemes, bodily images, speech forms, and thematic units, then coded in a matrix under four categories: language and speech, body and embodiment, personhood and self-awareness, and intention and accountability. Analysis proceeded through close reading, lexical-rhetorical analysis, thematic coding, interpretation through anthropological concepts of agency, indexicality, embodiment, and intention, and synthesis into an integrated model. Findings: The study finds that Sūrah al-Qiyāmah does not merely describe the Day of Resurrection as a future cosmic event but constructs a model of Qur’anic personhood. Language appears as moral action; the body functions as a semiotic site of identity and destiny; intention becomes readable through speech and conduct; and accountability exposes the whole human self before God. Research Implications: This article contributes to Qur’anic studies, linguistic anthropology, body studies, and Islamic moral psychology by offering an integrative model of personhood in Sūrah al-Qiyāmah and by demonstrating how interdisciplinary Qur’anic interpretation can connect textual structure with moral anthropology. KEYWORDS: Sūrah al-Qiyāmah, Linguistic anthropology, Personhood, Body semiotics, accountability.